EARLY MOLECULAR RESPONSE WITH IMATINIB THERAPY IN CHRONIC MYELOID LEUKEMIA AND ITS ASSOCIATION WITH BASELINE WHITE BLOOD CELL COUNT AND SPLEEN SIZE - Abdul Ali Wajid (Army Medical College Rawalpindi, 2018)
Objectives: To determine the frequency of early molecular response in patients of chronic myeloid leukemia treated with Imatinib and its association with baseline white blood cell (WBC) count and spleen size. Study Design: Cross sectional study. Place and Duration of Study: Combined Military Hospital, Rawalpindi Pakistan, from May to Nov 2017. Material and Methods: Seventy eight patients of Chronic Myeloid Leukemia (CML) in chronic phase (CP) were included in the study. Inclusion criteria were: 18 years or older, diagnosed with CML in CP with positive BCR ABL1. Patients who were in accelerated/blast phase, or already taking any Tyrosine Kinase Inhibitors or chemotherapy were excluded from the study. Base line WBC count, spleen size and BCR-ABL1 IS values were recorded. All the enrolled patients were placed on Imatinib therapy (400 mg/day) and RT-PCR for BCR ABL1 transcript was repeated after three months. Results: In our study, 60.15% of patients achieved EMR at 3 months after Imatanib therapy (p-value <0.001). In univariate analysis, there was significant association of spleen size, baseline WBC count and percentages of blasts in bone marrow with BCR ABL1 (IS) at 3 months (p-value <0.001), while on multivariate regression model, significant association was found only in spleen size (p-value <0.001) with EMR. Conclusion: A significant number of patients achieved EMR with Imatinib therapy. Spleen size at diagnosis was the only significant factor associated with achieving EMR. It is imperative to identify patients at an early stage who are unlikely to achieve EMR and therefore have poor over-all survival.